The lncRNA-mediated ceRNA network of Altica viridicyanea is involved in the regulation of the Toll/Imd signaling pathway under antibiotic treatment - Ren, Yipeng; Chen, Juhong; Wang, Yuan; Fu, Siying; Bu, Wenjun; Xue, Huaijun (Frontiers in Physiology, 2023)
Long noncoding RNAs (lncRNAs) play significant roles in the regulation of mRNA expression or in shaping the competing endogenous RNA (ceRNA) network by targeting miRNA. The insect gut is one of the most important tissues due to direct contact with external pathogens and functions in the immune defense against pathogen infection through the innate immune system and symbionts, but there are limited observations on the role of the lncRNA-involved ceRNA network of the Toll/Imd pathway and correlation analysis between this network and bacterial microbiota in the Altica viridicyanea gut. In this research, we constructed and sequenced six RNA sequencing libraries using normal and antibiotic-reared samples, generating a total of 17,193 lncRNAs and 26,361 mRNAs from massive clean data by quality control and bioinformatic analysis. Furthermore, a set of 8,539 differentially expressed lncRNAs (DELs) and 13,263 differentially expressed mRNAs (DEMs), of which related to various immune signaling pathways, such as the Toll/Imd, JAK/STAT, NF-κB, and PI3K-Akt signaling pathways, were obtained between the two experimental groups in A. viridicyanea. In addition, numerous GO and KEGG enrichment analyses were used to annotate the DELs and their target genes. Moreover, six Toll family members and nineteen signal genes from the Toll/Imd signaling pathway were identified and characterized using online tools, and phylogenetic analyses of the above genes proved their classification. Next, a lncRNA-miRNA-mRNA network of the Toll/Imd pathway was built, and it contained different numbers of DEMs in this pathway and related DELs based on prediction and annotation. In addition, qRT-PCR validation and sequencing data were conducted to show the expression patterns of the above DELs and DEMs related to the Toll/Imd signaling pathway. Finally, the correlated investigations between DELs or DEMs of the Toll/Imd signaling pathway and most changes in the gut bacterial microbiota revealed significantly positive or negative relationships between them. The present findings provide essential evidence for innate immune ceRNAs in the beetle gut and uncover new potential relationships between innate immune pathways and the gut bacterial microbiota in insects.